2011
DOI: 10.1063/1.3622772
|View full text |Cite
|
Sign up to set email alerts
|

Admissible shock waves and shock-induced phase transitions in a van der Waals fluid

Abstract: A complete classification of shock waves in a van der Waals fluid is undertaken. This is in order to gain a theoretical understanding of those shock-related phenomena as observed in real fluids which cannot be accounted for by the ideal gas model. These relate to admissibility of rarefaction shock waves, shock-splitting phenomena, and shock-induced phase transitions. The crucial role played by the nature of the gaseous state before the shock (the unperturbed state), and how it affects the features of the shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 44 publications
6
40
0
Order By: Relevance
“…with δ =R/c v ,R the gas constant, c v the constant volume specific heat, a and b the van der Waals coefficients, with K a suitable constant [23]. The evolution is governed by the conservation equations for mass …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…with δ =R/c v ,R the gas constant, c v the constant volume specific heat, a and b the van der Waals coefficients, with K a suitable constant [23]. The evolution is governed by the conservation equations for mass …”
mentioning
confidence: 99%
“…Away from the bubble, the shock propagates in the still liquid that, after the expansion wave, relaxed back to p ∞ , θ ∞ = θ e . The shock speed w is determined by the state ahead of the shock (p ∞ , ρ ∞ , u ∞ = 0) and by an additional parameter, the density ρ b behind the shock, say, see [28] and [23] for details concerning a van der Waals fluid. The small compressibility of the liquid…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(3.45); it corresponds to the limiting case of c V = ∞. Because we treat all the metastable states between the binodal and the spinodal on equal basis with the absolutely stable ones, we are interested in a broader region of negative non-linearity that would lie above the spinodal curve -in contrast to the one above the binodal analyzed by previous authors [17,18,19]. The boundary Γ = 0 of the NNL region in GWEOS is obtained by setting the numerator in Eq.…”
Section: Negative Non-linearity and Rarefaction Shocksmentioning
confidence: 89%
“…Recently [11] have studied evolutionary behaviour of acceleration waves in a perfectly conducting inviscid radiating gas permeated by a transverse magnetic field. Zhao et al [15], has shown that the shock waves in a van der Waal's fluid exhibit a richer behaviour than that predicted by the ideal gas model, characterizing compressive shocks, rarefaction shocks, and shock splitting phenomena together with their admissibility; the physical meaning of van der Waals gas and its influence on wave motion may be seen in the papers [17][18][19]. Ambika et al [20] have used the theory of progressive waves and some related procedures to study the attenuation and geometrical spreading of waves of finite and moderately small amplitudes influenced by the effects of non-linear convection in a non-ideal gas.…”
Section: Introductionmentioning
confidence: 99%